Efficiency Quality Index (EQI)—Implementing a Novel Metric That Delivers Overall Institutional Excellence and Value for Patients - Cerfolio, Robert J.; Chang, Stephanie H. (Frontiers in Surgery, 2021)
In the last decade, healthcare systems have shifted their focus from increased volume of patients and procedures to improving patient outcomes and quality. While there are many societies and companies that have surrogate measures of excellence, these metrics are determined by those who do not directly participate and fully understand the best measurements of quality. In order to better assess quality and value, the Efficiency Quality Index (EQI) was created. The novel aspect of the EQI is the determination of metrics by the physicians who actually perform the procedures, in order to create an accurate and fair measurement of performance and outcomes. In this article, we describe how to create and implement the EQI, as well as outline its benefits.